Wood ornamentation: characteristics of Yemeni traditional tower house opening in old city Sana’a, Yemen / Abu Bakar Abd Hamid ... [et al.] - Abd Hamid, Abu Bakar; Alias, Aida; Rahmat, Norashikin (2014)
The purpose of this research study is about the identity of wood ornamentation on openings in the traditional Yemeni tower houses in Old City Sana’a Yemen. This study is to identify the origin of the wood ornamentation on the residential openings as an indication for the public as information sources regarding the identification of the wood ornamentation on openings are limited descending to unavailable. In this approach, the collecting data will establish the types of ornamentation on the residential openings and identify the ornaments motifs, style and origin. This research started with the literature review on the general information of ancient, location, and character of ornamentation types. The study will describes variation of types and characters of ornamentation in Yemeni tower house openings. This study has preparing some method such as observations, measurements and interviews to investigate and analyses the ornament types, style and origin in tower house openings. All the information accumulated from the survey is collected and analyzed based on responses by the respondents. This study was concluded with occurred result and data analysis and also finding on Yemeni tower house opening types, outer openings or the gate adopted by the motifs and shapes from the craftsmanship. Furthermore, these studies were improving by related purpose of traditional ornament and the Islamic identity in house facade design in Yemeni tower house Old City Sana’a.